2019
DOI: 10.12968/ajmw.2018.0027
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence among pregnant women in Uganda

Abstract: Background: Intimate partner violence may be more prevalent during pregnancy as women are more vulnerable. Aims: To determine the prevalence of intimate partner violence and associated factors among pregnant women at Soroti Regional Referral Hospital, Uganda. Methods: A cross-sectional study was conducted among 180 pregnant women. Data were collected using a pre-tested, semi-structured questionnaire. Intimate partner violence was measured using the revised Conflict Tactile Scale 2. Findings: The overall preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 17 publications
2
15
1
Order By: Relevance
“…Intimate partner violence (40.6%) among pregnant teenagers in two health units in Lira district, northern Uganda is higher than the national prevalence (27.8%) among pregnant women (Epuitai et al, 2019) and the global prevalence of 30% among women in the general population (Jewkes et al, 2017). However, the prevalence of intimate partner violence in this study was lower (40.6%) compared to findings reported by several other studies.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Intimate partner violence (40.6%) among pregnant teenagers in two health units in Lira district, northern Uganda is higher than the national prevalence (27.8%) among pregnant women (Epuitai et al, 2019) and the global prevalence of 30% among women in the general population (Jewkes et al, 2017). However, the prevalence of intimate partner violence in this study was lower (40.6%) compared to findings reported by several other studies.…”
Section: Discussioncontrasting
confidence: 84%
“…The Kish Leslie formula was used to calculate the sample size (Straus, 2004). An intimate partner violence prevalence of 27.8% among pregnant women in Eastern Uganda, as reported by Epuitai et al (2019), was used for sample size estimation, assuming 80% power and 95% confidence intervals. This gave a sample size of 310 women.…”
Section: Population and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…In Nigeria, a study reported a 20% decrease in overall IPV prevalence (0.8%) during the first 6 weeks postpartum compared to the time during pregnancy (20.8%). Further four studies reported prevalence estimates of IPV during pregnancy and postpartum without providing any comparable estimates before and after childbirth ( 46 , 61 , 70 , 106 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only six studies investigated bidirectionality of IPV. In the studies focused on bidirectional IPV, two of these studies were during pregnancy ( 37 , 89 ), one study was during the postpartum period ( 46 ), and three studies were during both pregnancy and the postpartum period ( 42 , 58 , 66 ) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%